Formation Mechanism of Deposits in Rotary Kiln during Steelmaking Dust Carbothermic Recycling - Xiaobo Min; Luyu Huang; Maixin Yu; Yunyan Wang; Yong Ke; Cong Peng; Xu Yan; Qingyu Huang; Yun Li (Separations, 2024)
Rotary kiln has been widely used in hazardous waste treatment because of its strong adaptability to raw materials, high productivity, and simple processing technology. However, the formation of deposits reduces its performance period and profitability. This study characterized the deposit mineralogy and thermodynamically and experimentally investigated its formation mechanism. The results show that the main phases of the deposit are magnetite, monolithic iron, olivine, and yellow feldspar. They indicate that the deposit formation process was accompanied by the participation of alkaline and iron oxides. The intermediate product Ca2SiO4 can promote the generation of low melting point phases, such as CaFeSiO4 and Ca2Al2SiO7, which are the main phases of deposit materials. Additionally, the reduction intermediate product FeO facilitated the generation of a liquid ferrous mixture (Fe3O4-FeO and Fe3O4-FeO-Fe mixture), which in turn further promoted the growth of the initial deposit phase. The solid deposit formed and attached to the kiln inner wall, along with a decrease in temperature. These results are expected to provide an idea or approach for fundamentally solving the problem of deposits in the rotary kiln.